STATE OF THE SURFACE WATERS IN CROSS BORDER REGION OF EASTERN SERBIA AND CARAS SEVERIN COUNTY – MOLDOVA NOUA IN ROMANIA - STEVANOVIĆ, Zoran; KOVAČEVIĆ, Renata; MARKOVIĆ, Radmila; GARDIĆ, Vojka; VULPE, Bianca Constantina; BOROS, Bianca; MENGHIU, Gheorghita (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Bor, Krivelj, and Bela Rivers in Eastern Serbia belong to the watershed of Timok River, which is a tributary of Danube River. These Rivers flow near to the largest mining complex in Republic of Serbia. Rivers Bosneag, Radimna and Nera from the Romanian side in Caras Severin County near to Moldova Noua are also tributary of Danube and flow in area which is affected by spreading of dust from the abandoned flotation tailing of copper mine. This study includes environmental monitoring of the surface waters in considered Romania-Serbia cross border area during 2019-2020. Chemical analyses confirmed pollution mostly with heavy metals (Fe, Mn, Cu, Zn, As, Ni, Pb, Cd) closer to mines while with larger distance pollution decrease. The measured values were compared with Serbian and Romanian legislation which confirmed moderate and high pollution depending on category of surface waters. Measured Cd concentrations were of 9.51 - 5375 μg L-1 for the IV category of River water close to Bor mine. The main anthropogenic source in Eastern Serbia was Bor mine and smelter.